2022
DOI: 10.1111/1753-6405.13265
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ awareness of antimicrobial resistance: a qualitative study utilising the Health Belief Model in Perth, Western Australia

Abstract: Objective: This study aimed to determine local factors that promote or prevent parents' responsible use of antibiotics for their children in Perth, Western Australia. Methods:The Health Belief Model was used to guide this study. Four focus group discussions were conducted, with 26 participants. Participants were recruited purposively through a parent group organisation. The Framework Method was utilised to analyse the data.Results: Participants agreed that antimicrobial resistance (AMR) is a serious health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Furthermore, this study identified a relationship between individuals' education levels and their behavior regarding the use of antibiotics. This finding is not surprising, as previous research has also reported a similar connection between education and antibiotic use [64]. It is possible that individuals with a higher level of education have a better understanding of the risks associated with antibiotic misuse, and are therefore, more likely to exhibit responsible behaviors.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, this study identified a relationship between individuals' education levels and their behavior regarding the use of antibiotics. This finding is not surprising, as previous research has also reported a similar connection between education and antibiotic use [64]. It is possible that individuals with a higher level of education have a better understanding of the risks associated with antibiotic misuse, and are therefore, more likely to exhibit responsible behaviors.…”
Section: Discussionsupporting
confidence: 78%
“…Most people trust their family physician's perspectives [40]. Another study showed that participants who were involved in decisions on how to manage their children's illness by their GPs facilitated responsible use of antibiotics [41]. In studies conducted by Fathi et al and Mohsen et al, it was found that physicians and health staff were effective in promoting preventive behaviors [35,42].…”
Section: Discussionmentioning
confidence: 99%
“…The awareness of dangers deriving from the use of too many antibiotics is useful, but in some cases, it is not enough to combat the possible resistance. For example, in a study conducted in Australia on children, it was demonstrated that parental knowledge of antibacterial resistance does not generally translate into a responsible use of antibiotics for their children [ 37 ]. The inappropriate consumption and application of antibiotics have driven the rapid emergence of diverse resistant Gram-negative bacteria, including PDR, DTR, XDR, MDR, and CR Gram-negative bacteria ( Table 1 ) [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%